2020
DOI: 10.12659/msm.920537
|View full text |Cite|
|
Sign up to set email alerts
|

Quercetin Inhibits the Proliferation and Metastasis of Human Non-Small Cell Lung Cancer Cell Line: The Key Role of Src-Mediated Fibroblast Growth Factor-Inducible 14 (Fn14)/ Nuclear Factor kappa B (NF-κB) pathway

Abstract: Departmental sources Background:Quercetin (Que) is reported to induce apoptosis of lung cancer cells. Src is closely related to the progression of non-small cell lung cancer (NSCLC) and can be modulated by Que in macrophages. In the current study, the interaction between Que and Src signaling in NSCLC cells was explored to explain the anti-NSCLC function of Que. Material/Methods: NSCLC cell line HCC827 was subjected to the administrations of Que at different concentrations. The effect of Que on tumor cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Dong et al found that quercetin inhibited the expression of Src, and subsequently, inhibited Fn14/NF-kappa B signaling, thereby suppressing the proliferation and metastasis of NSCLC. This suggests that Src expression promotes NSCLC progression and could be a target for the treatment of NSCLC ( Dong et al, 2020 ). In the ErbB signaling pathway, the ErbB receptor family and its downstream pathways may regulate epithelial-mesenchymal transition, migration, and tumor invasion by regulating components of the extracellular matrix (ECM) ( Kern et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al found that quercetin inhibited the expression of Src, and subsequently, inhibited Fn14/NF-kappa B signaling, thereby suppressing the proliferation and metastasis of NSCLC. This suggests that Src expression promotes NSCLC progression and could be a target for the treatment of NSCLC ( Dong et al, 2020 ). In the ErbB signaling pathway, the ErbB receptor family and its downstream pathways may regulate epithelial-mesenchymal transition, migration, and tumor invasion by regulating components of the extracellular matrix (ECM) ( Kern et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibited cell proliferation and tumor growth [408,411,412]. Delayed appearance of lung adenocarcinoma [420].…”
Section: Quercetinmentioning
confidence: 99%
“…Quercetin dose-dependently suppressed HGF- and TGFα-induced migration of hepatocellular carcinoma cells by inhibiting the signaling pathway of AKT, but not p38 MAPK [ 413 ]. In non-small cell lung carcinoma models, quercetin inhibited proliferation and anchorage-independent growth by inhibiting the Src-mediated Fn14/NF-ĸB pathway both in vitro and in vivo [ 408 ] and improved the radiosensitivity of these cells by altering the expression of miR-16-5p and Wee1 [ 414 ]. In vivo, lung adenocarcinoma appearance was delayed and increased non-neoplastic body weight gain in mice with tumor oxidative stress after daily treatment with quercetin was observed [ 420 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…An in vivo study showed that Qu injection in A549 tumor-bearing mice efficiently repressed growth of cancer [ 160 ]. Generally, mostly studies on Qu concentrated on its growth inhibitory action through initiation of apoptosis [ 65 ] or autophagy [ 271 ] development of chemosensitivity [ 272 ] and Qu exerted the anti-NSCLC effect by inhibiting Src-mediated Fn14/NF- κ B pathway both in vitro and in vivo [ 273 ].…”
Section: Role Of Qu In Prevention and Inhibition Of Various Types mentioning
confidence: 99%